2018
DOI: 10.33023/jikeb.v4i1.151
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Usia Dengan Kejadian Abortus Pada Ibu Di Ruang Ponek Rsud Jombang

Abstract: Pendahuluan: Masalah kesehatan ibu hamil merupakan masalah yang perlu mendapatkan prioritas  utama, hal ini menunjukan bahwa beberapa kehamilan tidak berakhir dengan kelahiran akan tetapi banyak yang mengalami abortus, kejadian ini dipicu karena beberapa faktor diantaranya adalah usia ibu, yang dimana usia sehat kehamilan yank baik antara 20-35 tahun, karena usia tersebut paling baik untuk kesehatan seorang ibu agar menghindari terjadinya abortus. Tujuan penelitian ini adalah untuk mengetahui hubungan usia den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The results refuted some of the effects of previous studies that obstetric complications, including postpartum hemorrhage, generally occur in multiple pregnancies compared to singleton pregnancies due to factors such as increased uterine tension, low blood accumulation, mechanical pressure on the cervix, and premature rupture of membranes causing postpartum hemorrhage and death in mother and baby (17). However, the results of this study were supported by another study, which reported that postpartum hemorrhage was more common in mothers with single births than in mothers with more than one fetus (18). Based on the results of this study and some previous studies, it was concluded that postpartum hemorrhage can occur in all types of pregnancies.…”
Section: Discussionsupporting
confidence: 51%
“…The results refuted some of the effects of previous studies that obstetric complications, including postpartum hemorrhage, generally occur in multiple pregnancies compared to singleton pregnancies due to factors such as increased uterine tension, low blood accumulation, mechanical pressure on the cervix, and premature rupture of membranes causing postpartum hemorrhage and death in mother and baby (17). However, the results of this study were supported by another study, which reported that postpartum hemorrhage was more common in mothers with single births than in mothers with more than one fetus (18). Based on the results of this study and some previous studies, it was concluded that postpartum hemorrhage can occur in all types of pregnancies.…”
Section: Discussionsupporting
confidence: 51%
“…In addition, women who experiencing postpartum hemorrhage had a history of suffering from anemia during pregnancy [8].…”
Section: Introductionmentioning
confidence: 99%